1977
DOI: 10.1017/s1323358000015186
|View full text |Cite
|
Sign up to set email alerts
|

Observations of NH3 in Southern Sources

Abstract: Ammonia was the first interstellar molecule with more than two atoms to be discovered (Cheung et al. 1968). Since that time it has been observed in many HII regions and dark clouds (Mayer et al. 1973; Morris et al. 1973; Cheung et al. 1973; Kaifu et al. 1975). The molecule has a rich rotation-inversion spectrum with about 10 transitions in the range 23-25 GHz. Each line has hyperfine structure which permits, in principle, the determination of optical depths, filling factors and excitation. Unfortunately line b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the absence of MALT90, we use the molecular line information from earlier single pointing observations. The molecular line velocity is −12.0 km/s for CO and −11.7 km/s for CS observations, towards G351.63-1.25 (Batchelor et al 1977;Whiteoak, Otrupcek & Rennie 1982). However, being single dish and single pointing observations, its is difficult to segregate the emission from A and B regions.…”
Section: Bipolar Nature Of G35163-125mentioning
confidence: 91%
See 1 more Smart Citation
“…In the absence of MALT90, we use the molecular line information from earlier single pointing observations. The molecular line velocity is −12.0 km/s for CO and −11.7 km/s for CS observations, towards G351.63-1.25 (Batchelor et al 1977;Whiteoak, Otrupcek & Rennie 1982). However, being single dish and single pointing observations, its is difficult to segregate the emission from A and B regions.…”
Section: Bipolar Nature Of G35163-125mentioning
confidence: 91%
“…Detection of C172α emission towards outer regions where there is weak or no radio continuum emission suggests that these originate within regions whose physical properties such as ne, Te and emission measure (EM) are different from that of the PIM surrounding the H II region (e.g., Kantharia, Anantharamaiah & Goss 1998). From the molecular line data, the velocity of molecular cloud is estimated as ∼ −12 km/s (Batchelor et al 1977;Gardner & Whiteoak 1978).…”
Section: G35163-125mentioning
confidence: 99%
“…The associated molecular cloud was detected by Gillespie et al (1977) during their observations of southern Galactic H ii regions in the transition of CO. Similarly, interstellar molecules like OH (Caswell & Haynes 1975), H 2 O (Kaufmann et al 1977), NH 3 (Batchelor et al 1977), CS (Gardner & Whiteoak 1978) and H 2 CO (Gardner & Whiteoak 1984) were detected towards this region, indicating extremely dense molecular material. Several maser sources in the lines of H 2 O (Batchelor et al 1980; Braz & Scalise 1982; Braz et al 1989; Scalise, Rodriguez & Mendoza‐Torres 1989), OH (Caswell, Haynes & Goss 1980) and methanol (Macleod & Gaylard 1992; Schutte et al 1993; Caswell et al 1995; van der Walt, Gaylard & Macleod 1995; van der Walt et al 1996; Ellingsen et al 1996; Macleod et al 1998) have been detected towards this complex in independent surveys and observations towards selected IRAS sources.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to the IRAS maps at the mid and far-infrared wavebands, far-infrared (FIR) balloon-borne observations (1 ′ angular resolution) of the dust continuum at 150 and 210 µm (Karnik et al 2001) identified 23 emission peaks with dust temperatures between 20 and 40 K. Largescale CO(1-0) observations by Bronfman et al (1989) with an angular resolution of 9 ′ obtained a global view of the molecular gas distribution in this region. However most of the remaining spectroscopic observations toward this GMC are primarily pointed mode observations of the emissions of the lines of CO (Gillespie et al 1977;Brand et al 1984), CS (Gardner & Whiteoak 1978;Bronfman et al 1996), H 2 CO (Gardner & Whiteoak 1984), NH 3 (Batchelor et al 1977), H 2 O, OH and methanol masers (Braz & Epchtein 1983;Caswell 1997;Walsh, Hyland, Robinson, & Burton 1997) toward predetected H  regions and IRAS sources. These observations suggest ongoing high-mass star formation activity and enhanced density cores associated with most of the strong emission peaks.…”
Section: Introductionmentioning
confidence: 99%